GAMBARAN KECEMASAN DAN PENYEBAB KECEMASAN PADA IBU HAMIL DI PUSKESMAS UMBAN SARI PADA MASA PANDEMI COVID-19 - Sonia Dewita; Erika Erika; Oswati Hasanah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Pregnant women are listed as one of the vulnerable groups at risk of infection with Covid-19, and the current pandemic conditions have made pregnant women anxious. The objective of this research was to describe the anxiety and causes of anxiety in pregnant women at the Umban Sari Health Center during the Covid-19 pandemic. Method: The research method used was simple descriptive. This research was carried out in the work area of Umban Sari Health Center, with a total sample of 80 pregnant women obtained using a purposive sampling technique. The Perinatal Anxiety Screening Scale questionnaire was used as a measuring tool, univariate analysis was used. Results: The majority of respondents (42.5%). The cause of anxiety was that 60.8% of respondents were concerned about conctracting Covid-19 from other patients who checked their pregnancies, 53.8% were concerned about childbirth with few visitors, and 68.8% were concerned about not receiving the expected service, the cause of anxiety was that 28.8% experienced mild anxiety at non high risk ages, 30% in multigravida pregnancies, and 17.5% in the second trimester, reported mild anxiety. Conclusion: Pregnant women’s anxiety is mild anxiety, which health service, age, gravida and gestational age was the causes of anxiety.